SPECTROSCOPIC AND CHEMICAL EVALUATION OF CLAY MINERALS AND THEIR SUITABILITY FOR THE MANUFACTURING OF ORGANIC CLAY, MEDICINAL CLAY AND PILLARED CLAY - Mannan, Abdul; Hussain, S Imtiaz; Ehsan, Sadia; Khan, Muhammad Shafiq (Biological Sciences - PJSIR, 2004)
The levels of trace elements concentration of the clay minerals of Pakistan have been determined. Inductively Coupled Plasma (ICP) spectrometer was used for the determination of trace elements. The samples of the clay minerals were digested in the ETHOS microwave oven at 180 ± 5°C. The trace elements (As, Co, Cu, Cr, Cd, Fe, Mn, Ni, Pb, Se and Zn) 2 3 2 2 3 2 3 2 in the clay minerals of Pakistan fall within the global range. Except as all the trace elements fall within the technical specification of the medicinal clay. The chemical analysis also shows that (SiO , Al O , Fe O , CaO, MgO, Na O, and K O) these are within the technical specification of the medicinal clay. Therefore, at present they can be used for external use only. The trace elements (As, Co, Cu, Cr, Cd, Fe, Mn, Ni, Pb, Se and Zn) of clay mineral as well as the activated clay minerals were determined and it is observed that during activation Na, K and Ca ions are leached out. The presence of trace elements of transition metals which are used as catalysts in organic synthesis clearly demonstrate that the catalytic activity of clay minerals is due to these elements. If any of these elements is more than 1% in these clays minerals the clay will act as catalysts without activation. If the quantity of these trace elements is very small and leached out during activation the clay become inactive which is not explained by some workers. Pakistani clays are suitable for making pillared clays. At 550°C, the clay minerals are dehydroxylated and they act as Lewis acid and work as a catalyst in place of AlCl . It is observed that the clay minerals make complexes with ionic or non ionic surfactant very easily. These complexes make stable suspension in water and oil. It was observed that alkyl group gives a very good organic clay with a swelling property and stable suspension and is superior to the imported clay.